2021
DOI: 10.1093/sleep/zsab018
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability during wakefulness as a marker of obstructive sleep apnea severity

Abstract: Study Objectives Patients with obstructive sleep apnea (OSA) exhibit heterogeneous heart rate variability (HRV) during wakefulness and sleep. We investigated the influence of OSA severity on HRV parameters during wakefulness in a large international clinical sample. Methods 1247 subjects (426 without OSA and 821 patients with OSA) were enrolled from the Sleep Apnea Global Interdisciplinary Consortium. HRV parameters were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…Guidelines for measurement have been published, as well as some normal values ( Shaffer and Ginsberg, 2017 ), of which nocturnal values are given from the Hypnolaus study ( Berger et al, 2022 ). Various aspects of HRV were explored as short term values ( Lee et al, 2018 ), values in women ( Kesek et al, 2009 ), values in periodic leg movements ( Sforza et al, 2005 ), in patients suffering OSA ( Qin et al, 2021 ), and in those presenting with metabolic syndrome ( Assoumou et al, 2012a ).…”
Section: Autonomic Nervous System An Easy Toolmentioning
confidence: 99%
“…Guidelines for measurement have been published, as well as some normal values ( Shaffer and Ginsberg, 2017 ), of which nocturnal values are given from the Hypnolaus study ( Berger et al, 2022 ). Various aspects of HRV were explored as short term values ( Lee et al, 2018 ), values in women ( Kesek et al, 2009 ), values in periodic leg movements ( Sforza et al, 2005 ), in patients suffering OSA ( Qin et al, 2021 ), and in those presenting with metabolic syndrome ( Assoumou et al, 2012a ).…”
Section: Autonomic Nervous System An Easy Toolmentioning
confidence: 99%
“…High increases in heart rate following apneic events are associated with 30-60% increases in mortality risk and nonfatal/fatal cardiovascular disease compared to normal heart rate responses (Azarbarzin et al, 2020). New evidence also suggests that heart rate variability during wakefulness could be a useful marker of OSA severity and excessive daytime sleepiness, whereby OSA severity is associated with reduced and less complex dynamics of heart rate variability (Qin et al, 2021). Pulse wave amplitude (a marker of vasoconstriction in the finger) features (e.g., amplitude, frequency) have been associated with hypertension, cardiovascular events and diabetes (Hirotsu et al, 2020).…”
Section: Autonomic Signalsmentioning
confidence: 99%
“…Another meta-analysis, including 19 medium-to-high quality RCTs, also demonstrated that mind–body practice could significantly benefit HRV parameters and improve sympathetic–vagal balance [ 123 ]. Higher HRV during wakefulness is associated with higher sleep efficiency and better sleep quality [ 124 , 125 , 126 ]. Therefore, the action of HRV alteration may be an important mechanism by which MBM ameliorates the symptoms of insomnia or poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%